Diseño de un programa de salud de diagnóstico y tratamiento para pacientes diabéticos e hipertensos del centro de medicina familiar Vozandes ubicado en Carapungo norte de Quito provincia de Pichincha - Jiménez González, Henry Nelson (2015)
The research developed in this work is based on management by objectives. This research has as its ultimate purpose, the design of a health program concerning the diagnosis and treatment of diabetic and hypertensive patients of the Vozandes Family Healthcare Center, located in the Province of Pichincha, Carapungo North of Quito. To do this was conducted market research together with the technical study and financial economic evaluation. The market research report shows that there is an unmet demand for diagnostic services and treatment for diabetic and hypertensive patients. Currently this service as an ongoing plan does not exist, for this reason it is essential that a general medical consultation is taking place in Carapungo- Vozandes Family Healthcare Center, because many people in the community need this service. Regarding the technical study, the results showed that there is not any drawbacks to provide this service at an affordable cost. A key part of funding is through the method of administration of HCJB group, which are to whom belongs the Carapungo- Vozandes Family Healthcare Center, they have excellent trained staff, appropriate infrastructure and technology that allows providing a quality service. Through economic and financial evaluation it was determined that the project if feasible, capital recovery is acceptable and profitability for shareholders is adequate and reasonable. Since this is a non-profit company, the money generated will be reinvested to improve the infrastructure of the center, and the acquisition and implementation of medical services for the care of people with diabetes and high blood pressure.